2017
DOI: 10.1002/asi.23854
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and learning outcomes of online news engagement

Abstract: User engagement (UE) is a quality of user experience characterized by the depth of an actor's cognitive, temporal, and/or emotional investment in an interaction with a digital system. Currently more art than science, UE has gained theoretical and methodological traction over the past decade, yet there is still a need to establish empirical links between UE and desired outcomes (e.g., learning, behavior change), and to understand the myriad user, system, contextual, and so on, factors that predict successful di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…After applying this scale to different fields, such as online shopping (O'Brien, 2010) and Facebook (Banhawi and Mohamad Ali, 2011), it was concluded that the initial six factors should be reduced to four: focused attention, perceived usability, aesthetic appeal and a fourth one that covers the original factors of endurability, novelty and perceived involvement. It has also been proven that only subscales suited to the distinctive features of the subject of study should be considered (O'Brien, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After applying this scale to different fields, such as online shopping (O'Brien, 2010) and Facebook (Banhawi and Mohamad Ali, 2011), it was concluded that the initial six factors should be reduced to four: focused attention, perceived usability, aesthetic appeal and a fourth one that covers the original factors of endurability, novelty and perceived involvement. It has also been proven that only subscales suited to the distinctive features of the subject of study should be considered (O'Brien, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the earliest definitions proposed that "user engagement is a user's response to an interaction that gains, maintains and encourages their attention, particularly when they are intrinsically motivated" [20]. Further definitions are given by various authors (eg, [9,[18][19][20][21][22]), and a certain overlap of aspects is apparent. For the purpose of this study, the following commonly cited principles were considered.…”
Section: Concept Of User Engagementmentioning
confidence: 99%
“…For the purpose of this study, the following commonly cited principles were considered. User engagement is a quality of user experience [21,22] and is multidimensional [9,18,22]. There is no consensus concerning the meaning of the dimensions, but the cognitive, emotional, and behavioral dimensions are prevalent in user engagement literature [11,14,23].…”
Section: Concept Of User Engagementmentioning
confidence: 99%
“…Several aspects of content have been investigated in conjunction with UE, including sentiment, interest, novelty, quality and message framing (O'Brien, 2017). Digital content has been proven to play a significant role in influencing consumers' behavior online .…”
Section: Endurability and Rewardmentioning
confidence: 99%
“…Despite current research, a shared understanding of how to usefully conceptualize engaging content is lacking. Current research is focused on identifying and evaluating UE, but not on the actual development of engaging experiences (O'Brien, 2017;O'Brien & Cairns, 2016). Content is not well situated in current theory and not thoroughly researched as a determinant of UE.…”
Section: Endurability and Rewardmentioning
confidence: 99%